2002
DOI: 10.1002/1521-3765(20021216)8:24<5684::aid-chem5684>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Charged and Neutral NO3 Isomers from the Ionization of NOx and O3 Mixtures

Abstract: Mass spectrometric techniques have been utilized in conjunction with theoretical methods to detect and characterize new species formed upon ionization of gaseous mixtures containing ozone and an NO x oxide. NO 5 as well as isomeric NO 4 and NO 3 ions have been identified. Moreover, utilization of neutralization reionization mass spectrometry (NRMS) has provided strong evidence for, if not a conclusive demonstration of, the existence of a new NO 3 isomer, in addition to the long-known trigonal radical, as a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…These calculations indicated that such a complex must be very weakly bound, inconsistent with the identification of a more strongly bound complex by Bhatia and Hall. 54 Recent microwave spectroscopic and theoretical studies by Watson et al 59 support the existence of one or more weakly bound complexes of O 2 with NO, as do neutralization-reionization studies by Cacace et al 60 The NO-stretching absorption of the complex proposed in the present discussion has a suitably small shift from the fundamental absorption of uncomplexed NO to correspond with the frequency pattern calculated by Eisfeld and Morokuma 58 for trans-OONO. However, the observed OOstretching absorption is much closer to that of uncomplexed O 2 than is the calculated value, suggesting that the complex is more weakly bound than is predicted by the CCSD calculations.…”
Section: Stabilization Of An "O 2 …"No… Interaction Productmentioning
confidence: 99%
“…These calculations indicated that such a complex must be very weakly bound, inconsistent with the identification of a more strongly bound complex by Bhatia and Hall. 54 Recent microwave spectroscopic and theoretical studies by Watson et al 59 support the existence of one or more weakly bound complexes of O 2 with NO, as do neutralization-reionization studies by Cacace et al 60 The NO-stretching absorption of the complex proposed in the present discussion has a suitably small shift from the fundamental absorption of uncomplexed NO to correspond with the frequency pattern calculated by Eisfeld and Morokuma 58 for trans-OONO. However, the observed OOstretching absorption is much closer to that of uncomplexed O 2 than is the calculated value, suggesting that the complex is more weakly bound than is predicted by the CCSD calculations.…”
Section: Stabilization Of An "O 2 …"No… Interaction Productmentioning
confidence: 99%
“…Moreover, it is interesting to note that the adiabatic ionization energy for the nitrate radical NO 3 as determined to be 12.57 ± 0.03 eV by Monks et al [21] using a discharge flow-photoionization mass spectrometer apparatus coupled to a synchrotron radiation source is well below the present appearance energy, thus excluding contamination of the N 2 O 5 target with the nitrate radical. It should be noted that the structure and the atmospheric implications of the existence of the NO 3 + cation has been extensively studied and discussed recently [22].…”
Section: Resultsmentioning
confidence: 99%
“…NO 5 ϩ and isomeric NO 4 ϩ and NO 3 ϩ ions have been identified, and NRMS has provided evidence for the existence of a new isomer of NO 3 . 24 The gas phase structure of O-nitrobis(trifluoromethyl)hydroxylamine, (F 3 C) 2 NONO 2 , has been determined by electron diffraction. The molecule contains a very long O-N bond, which can be rationalised on the basis of weak bonding between the stable radicals (CF 3 ) 2 NO and NO 2 .…”
Section: Nitrogenmentioning
confidence: 99%